2018
DOI: 10.1038/s41598-018-22096-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characteristics of 251 consecutive patients with macular and cone/cone-rod dystrophy

Abstract: Macular and cone/cone-rod dystrophies (MD/CCRD) demonstrate a broad genetic and phenotypic heterogeneity, with retinal alterations solely or predominantly involving the central retina. Targeted next-generation sequencing (NGS) is an efficient diagnostic tool for identifying mutations in patient with retinitis pigmentosa, which shows similar genetic heterogeneity. To detect the genetic causes of disease in patients with MD/CCRD, we implemented a two-tier procedure consisting of Sanger sequencing and targeted NG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
145
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 169 publications
(177 citation statements)
references
References 68 publications
15
145
1
2
Order By: Relevance
“…There are currently 261 genes listed with established links to RDs (http://www.sph.uth.tmc.edu/RetNet/). Several studies have shown a rather high diagnostic yield (50%‐79%) of multigene panels in patients with RD . However, those cohorts were not selected on the basis of a particular mode of inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently 261 genes listed with established links to RDs (http://www.sph.uth.tmc.edu/RetNet/). Several studies have shown a rather high diagnostic yield (50%‐79%) of multigene panels in patients with RD . However, those cohorts were not selected on the basis of a particular mode of inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…In literatures, different autosomal recessive phenotypes have been associated with the CDHR1 gene mutations, ranging from RP to CRD although the relationship between phenotypes and gene mutations are variable . The proband in our study, with a loss of more than one‐thirds of CDHR1 by a homozygous and nonsense variant p.Y547*, has been noticed the simultaneous onset of dark adaptation difficulties, trouble with color vision, and light sensitivity at age of 24; ERG in different waves showed markedly reduced rod‐and‐cone responses; FP/FPP showed macular dysdrophy (MD).…”
Section: Discussionmentioning
confidence: 51%
“…Clinically, this patient presented MD/CRD. Thus, combined with our study, patients with CDHR1 truncated protein by nonsense, splicing variants or deletions with frameshift, other than missense variants, might cause more severely phenotypes, such as MD/CRD, and/or earlier disease onset …”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations